Aerial Photography Specifications for Himalayan Forest with Special Reference to Jammu and Kashmir - Tomar, M. S. (Indian Forester, 1971)
Nature of topography, composition and distribution of forests, objectives of photo interpretation and scale of the forest maps to be prepared are some of the important considerations for determining the scale of photography, camera and focal length of the lens to be used and season of photography. For coniferous forests of Himalayas a scale of 1:25,000 to 1:30,000 for aerial photography is suggested. Scale larger than this may not be practicable for large area survey due to mountaineous nature of the terrain. The suitable season for aerial photography appears to be October-November.